2015
DOI: 10.4238/2015.november.18.18
|View full text |Cite
|
Sign up to set email alerts
|

Meloxicam increases intracellular accumulation of doxorubicin via downregulation of multidrug resistance-associated protein 1 (MRP1) in A549 cells

Abstract: ABSTRACT. It has been suggested that selected COX inhibitors can overcome multidrug resistance through the inhibition of ATP-binding cassette-transporter proteins thereby enhancing the inhibitory effect of doxorubicin on human tumor growth and promoting the actions of cytostatics. However, their effect on lung cancer and the molecular mechanisms involved in the overcoming of multidrug resistance are unclear. In the present study, the ability of meloxicam, a COX-2-specific inhibitor to enhance doxorubicin-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…The protein kinase C activator and COX-2 inducer phorbol 12-myristate 13-acetate (PMA; 10 nM; Figure 3) induced MRP1 expression in MRP1-overexpressing A549 cells. 218 This could functionally be confirmed as PMA slightly decreased daunorubicin accumulation in MRP1-overexpressing 2R120 cells, but not in GLC 4 /ADR cells at 20 nM. 131…”
Section: Surface Active Agentsmentioning
confidence: 92%
“…The protein kinase C activator and COX-2 inducer phorbol 12-myristate 13-acetate (PMA; 10 nM; Figure 3) induced MRP1 expression in MRP1-overexpressing A549 cells. 218 This could functionally be confirmed as PMA slightly decreased daunorubicin accumulation in MRP1-overexpressing 2R120 cells, but not in GLC 4 /ADR cells at 20 nM. 131…”
Section: Surface Active Agentsmentioning
confidence: 92%
“…The newest report on this has been made by Chen et al. reporting on meloxicam and celecoxib . The in vitro approach in A549 cells showed that 10 μM meloxicam was superior compared to 10 μM celecoxib when it came to potentiate the toxicity of doxorubicin.…”
Section: Pharmacological and Experimental Drugs And Synthetic Analogsmentioning
confidence: 99%
“…The 1 mL DEX-SS-IND/DOX micelle solution was transferred into a dialysis membrane (MWCO 7.0 kDa) and then immersed in 20 mL incubation media with constant shaking at 70 rpm at 37°C. At predetermined time intervals (1,2,4,6,8,10,12,24,36, and 48 hours), the samples were collected and replaced with fresh medium. DOX content was measured using fluorescence spectrophotometry.…”
Section: Synthesis and Characterization Of Dex-ss-indmentioning
confidence: 99%
“…6,7 The antitumor agent doxorubicin (DOX) is widely used for the treatment of various solid tumors via interacting with DNA through intercalation and inhibiting topoisomerase II, but it is also a substrate for MRPs. 8 The abnormal increase of drug efflux and reduced intracellular drug concentration lead to DOX resistance. In addition, it has several therapeutic limitations, including irreversible nephrotoxicity, neurotoxicity, and cardiotoxicity.…”
Section: Introductionmentioning
confidence: 99%